EFEKTIFITAS PENGGUNAAN METODE DRILL DALAM PEMBELAJARAN SENI BACA AL-QUR’AN - Zulfahmi; Saifuddin A Gani; Fannia Hidayati (Genderang Asa: Journal of Primary Education, 2022)
Determining the right learning method is one of the keys to the success of teachers in transferring knowledge to their students. The drill method is a teaching method in which students carry out training activities, so that students have higher dexterity or skills than what has been learned. For this reason, this paper aims to examine more deeply the benefits and effectiveness of using the drill method in learning the art of reading the Qur'an for elementary school children. This research was conducted in Aceh Besar District, Suka Makmur District, Baet Mesjid Village, namely at one of the Al-Qur'an Reading Arts Institutes. The results of the study can be concluded that one of the effective methods used by teachers in learning the art of reading the Qur'an is the drill method. The use of the drill method will make it easier for teachers to convey the material and students easily understand the material and teachers can directly monitor the abilities of their students.